Eslicarbazepine acetate as adjunctive therapy in clinical practice: ESLADOBA study. (8th February 2017) - Chaves, J.; Breia, P.; Pimentel, J.; Pelejão, R.; Carvalho, M.; Mateus, P.; Grebe, H.; Mestre, A.; Fernandes, H.; Sousa, R.; Gala, A.
Abstract : Objective: To assess seizure control and tolerability of eslicarbazepine acetate (ESL) as adjunctive therapy to one baseline antiepileptic drug (AED), in adults with partial‐onset seizures (POS) with or without secondary generalization. Methods: Multicenter, non‐interventional, prospective cohort study conducted between March 2012 and September 2014 at 12 neurology departments in Portugal. Adults with POS not controlled with one AED who had initiated ESL as adjunctive treatment were enrolled. Retention rate was defined at the final visit (Vfinal) 6‐9 months of follow‐up. Proportion of responders, seizure‐free, changes in seizure frequency were evaluated using patients' diaries. Clinical Global Impression of Change (CGI‐C) and Clinical Global Impression of Severity (CGI‐S) were assessed by the neurologist. Results: Fifty‐two patients (48.1% male) were included with mean age 41.5±13.3 years. Mean epilepsy duration was 18.5±14.8 years; mean seizure frequency in the four previous weeks to baseline was 7.5±12.7. At Vfinal, retention rate was 73.0%; responder rate and seizure‐free rates were 71.1% and 39.5%, respectively. The median relative reduction in seizure frequency between baseline and Vfinal was 82.2%. A reduction in epilepsy severity (CGI‐S) was observed in 42.1%. According to CGI‐C, 73.6% patients had their epilepsy "much improved" or "very much improved". Twelve patients (23.1%) had at least one adverse event (AE), two (3.9%) had one serious AE, and five (9.6%) discontinued due to AE. Conclusions: Eslicarbazepine acetate showed good retention rates, elicited a significant reduction in seizure frequency, and was well tolerated when used in the clinical practice.